Method for reducing residual alkali on surface of high-nickel positive electrode material and coating method, prepared high-nickel positive electrode material and secondary battery
By placing the high-nickel positive electrode material in the LiOH-aluminum sol mixture for treatment, the problem of high-nickel positive electrode material with high-nickel positive electrode material is solved, and the preparation of high-nickel positive electrode material with low-residual alkali and alumina coated is realized, thereby improving the cycle performance and safety of the battery.
Patent Information
- Application Number
- CN202411994934.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The high content of LiOH and Li2CO3 on the surface of high nickel positive electrode materials endangers the battery cycle performance and safety performance, and the prior art is difficult to effectively reduce the residual alkali and maintain capacity.
The high-nickel positive electrode material was placed in the LiOH-aluminum sol mixture, and was subjected to pressure filtering, drying and sintering to form a high-nickel positive electrode material with low residue alkali and alumina coated.
Effectively remove LiOH and Li2CO3 on the surface of high-nickel positive electrode material, optimize the crystal structure and electrochemical performance of the material, and improve the cycle performance and safety of the battery.
Smart Images

Figure CN119764418A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a method for reducing residual alkali and coating on the surface of a high-nickel positive electrode material, and a prepared high-nickel positive electrode material and a secondary battery. Background Art
[0002] As the main positive electrode material of lithium-ion batteries, high-nickel positive electrode materials have high content of LiOH and Li2CO3 on their surface, which endangers the battery cycle performance and safety performance. Therefore, reducing the residual alkali content and increasing / maintaining the capacity unchanged have become a focus of current high-nickel positive electrode research. At present, most processes use pure water or other inorganic / organic solutions for washing and then coating and sintering. This process firstly causes the surface and near-surface area of the high-nickel positive electrode material to be delithiated by direct water washing, i.e. Li + With water H + Exchange occurs, protons migrate inward, causing the layered crystal material to shrink in a direction perpendicular to the transition metal layer and the oxygen layer, while lithium migrates outward, reducing the electrochemically active lithium of the material and causing loss of capacity; secondly, water washing can lead to reconstruction of the surface layer of the high-nickel material to form a NiO rock salt phase, which will increase the surface resistance and reduce the rate performance. Secondly, many studies have also adopted a dry coating process without water washing to reduce alkali. This process has little effect on reducing Li2CO3 and has certain safety hazards to the battery cell; at the same time, the process of washing and then coating and sintering extends the production time and cost. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the above technical background and provide a method for reducing the residual alkali and coating on the surface of high-nickel positive electrode materials, as well as the prepared high-nickel positive electrode materials and secondary batteries.
[0004] The invention provides a method for reducing residual alkali on the surface of a high-nickel positive electrode material and coating, comprising the following steps: placing the high-nickel positive electrode material in a LiOH-aluminum sol mixed solution, mixing and stirring, performing filter pressing and drying, and then sintering the dried product to obtain a high-nickel positive electrode material with low residual alkali and aluminum oxide coating.
[0005] The invention provides a low-residual-alkali and coated high-nickel positive electrode material obtained by the method.
[0006] The present invention provides a secondary battery, which comprises the low residual alkali and coated high nickel positive electrode material or the low residual alkali and coated high nickel positive electrode material prepared by the above method.
[0007] The present invention has the following beneficial effects.
[0008] The present invention provides a method for reducing residual alkali and coating on the surface of high-nickel positive electrode materials, and the prepared high-nickel positive electrode materials and secondary batteries. The method for reducing residual alkali and coating on the surface of high-nickel positive electrode materials provided by the present invention comprises: preparing low residual alkali and coating modified high-nickel positive electrode materials using the preparation method provided by the present invention, placing the high-nickel positive electrode materials in a LiOH-aluminum sol mixed solution, mixing and stirring, filtering and drying, and then sintering the dried product. The above method uses the LiOH-aluminum sol mixed solution to wash and remove LiOH and Li2CO3 on the surface of the high-nickel positive electrode material, and the alkaline LiOH solution can reduce the lattice Li + With water H + The exchange of water weakens the damage to the surface lattice of the material; at the same time, the surface of the high-nickel positive electrode material will be covered with aluminum sol, which will form a stable alumina coating after sintering, thereby optimizing the crystal structure and electrochemical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0010] Figure 1 It is a comparison chart of high temperature cycle performance curves of Examples 1-4 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION
[0011] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0012] The following is a detailed description of a method for reducing residual alkali and coating on the surface of a high-nickel positive electrode material, and the prepared high-nickel positive electrode material and secondary battery provided in an embodiment of the present invention.
[0013] In the first aspect, an embodiment of the present invention provides a method for reducing residual alkali and coating on the surface of a high-nickel positive electrode material, comprising the following steps: placing the high-nickel positive electrode material in a LiOH-aluminum sol mixed solution, mixing and stirring, filtering and drying, and then sintering the dried product to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0014] In some optional embodiments, the LiOH-aluminum sol mixture is prepared by dissolving LiOH in pure water to form an alkaline solution, and then adding aluminum sol and mixing and stirring.
[0015] In some optional embodiments, the concentration of Li in the alkaline solution + is 500 - 4000 ppm, and the solvent is pure water. Controlling the concentration of Li in the alkaline solution within an appropriate range can reduce the exchange of Li in the lattice of the high-nickel cathode material with H in water + and prevent the surface layer reconstruction of the high-nickel cathode material due to excessive water content, thereby reducing its rate performance. + with H in water +
[0016] In some optional embodiments, the chemical formula of the aluminum sol is a(Al2O3·nH2O)·bH x ·cH2O, where b < a, c, n, and Al2O3·nH2O is hydrated alumina; the concentration of hydrated alumina in the LiOH-aluminum sol mixture is 0.2 - 2 wt%, and the solvent is pure water.
[0017] In some optional embodiments, the mass ratio of the high-nickel cathode material to the LiOH-aluminum sol mixture is 1:(0.6 - 2). Controlling the mass ratio of the high-nickel cathode material to the LiOH-aluminum sol mixture within an appropriate range can dissolve LiOH and Li2CO3 on the surface of the high-nickel cathode material in the water of the LiOH-aluminum sol mixture and be washed away. If the mass ratio is too high, the amount of alkali washed away is not obvious due to too little LiOH-aluminum sol mixture. If the mass ratio is too low, too much LiOH-aluminum sol mixture will cause more lattice lithium to be washed away.
[0018] In some optional embodiments, the stirring time after mixing is 1 - 5 min.
[0019] In some optional embodiments, the drying temperature is 100°C - 150°C, and the time is 3 - 6 h; the sintering atmosphere is oxygen, the temperature is 500°C - 600°C, and the time is 3 h - 8 h. Controlling the sintering temperature within an appropriate range can, first, make the surface coating tightly combine with the high-nickel cathode material, and second, avoid secondary crystallization of the high-nickel cathode material at too high a temperature, resulting in further growth of the particles and attenuation of performance.
[0020] In some optional embodiments, the composition of the high-nickel cathode material is LiNi x Co y Mn z Me 1-(x+y+z) O2, where x ≥ 0.8, 0 ≤ y ≤ 0.2, 0 ≤ z ≤ 0.2, x + y + z ≤ 1, and Me includes one or more of Zr, Mg, Al, Ga, Ti, Nb, Mo, and W.
[0021] In a second aspect, an embodiment of the present invention provides a low residual alkali and alumina-coated high nickel positive electrode material prepared by the above method.
[0022] In a third aspect, an embodiment of the present invention provides a secondary battery, comprising the above-mentioned low residual alkali and alumina-coated high nickel positive electrode material or the low residual alkali and alumina-coated high nickel positive electrode material prepared by the above-mentioned method.
[0023] The present invention will be further described below in conjunction with the embodiments.
[0024] Example 1
[0025] 27g LiOH·H2O (concentration 56.7%) was added to 2.95L pure water and stirred to form a solution, and 60g aluminum sol (solid content 10%) was added to form a LiOH-aluminum sol mixed solution, wherein: Li + The concentration is 1500ppm, the concentration of hydrated alumina is 0.2wt%; with a solid-liquid ratio of 1:1, weigh 3kg of chemical formula LiNi 0.92 Co 0.05 Mn 0.03 The O2 positive electrode material was added to the above-mentioned mixed solution, stirred and washed for 1 minute, and immediately solid-liquid separation was performed using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3 hours, and then sintered at 600°C for 8 hours under pure oxygen to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0026] Example 2
[0027] 45g of LiOH·H2O (concentration 56.7%) was added to 2.95L of pure water and stirred to form a solution, and 60g of aluminum sol (solid content 10%) was added to form a LiOH-aluminum sol mixed solution, wherein: Li + The concentration is 2500ppm, the concentration of hydrated alumina is 0.2wt%; with a solid-liquid ratio of 1:1, weigh 3kg of chemical formula LiNi 0.92 Co 0.05 Mn 0.03 The O2 positive electrode material was added to the above-mentioned mixed solution, stirred and washed for 1 minute, and immediately solid-liquid separation was performed using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3 hours, and then sintered at 600°C for 8 hours under pure oxygen to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0028] Example 3
[0029] 27g LiOH·H2O (concentration 56.7%) was added to 2.95L pure water and stirred to form a solution, and 60g aluminum sol (solid content 10%) was added to form a LiOH-aluminum sol mixed solution, wherein: Li + The concentration is 1500ppm, the concentration of hydrated alumina is 0.2wt%; with a solid-liquid ratio of 1:1.5, weigh 2kg of chemical formula LiNi 0.92 Co 0.05 Mn 0.03 The O2 positive electrode material was added to the above-mentioned mixed solution, stirred and washed for 1 minute, and immediately solid-liquid separation was performed using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3 hours, and then sintered at 600°C for 8 hours under pure oxygen to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0030] Example 4
[0031] 27g LiOH·H2O (concentration 56.7%) was added to 2.46L pure water and stirred to form a solution, and 600g aluminum sol (solid content 10%) was added to form a LiOH-aluminum sol mixed solution, wherein: Li + The concentration is 1500ppm, the concentration of hydrated alumina is 2wt%; with a solid-liquid ratio of 1:1, weigh 3kg of chemical formula LiNi 0.92 Co 0.05 Mn 0.03 The O2 positive electrode material was added to the above-mentioned mixed solution, stirred and washed for 1 minute, and immediately solid-liquid separation was performed using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3 hours, and then sintered at 600°C for 8 hours under pure oxygen to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0032] Comparative Example 1
[0033] Weigh 3kg of chemical formula LiNi 0.92 Co 0.05 Mn 0.03 The O2 positive electrode material was directly added into 2.95L pure water, stirred and washed for 1min, and immediately subjected to solid-liquid separation using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3h, and then sintered at 600°C for 8h under pure oxygen to obtain a high nickel positive electrode material with low residual alkali.
[0034] Comparative Example 2
[0035] 27g LiOH·H2O (concentration 56.7%) was added to 2.95L pure water and stirred to form a solution without adding aluminum sol, wherein the Li concentration was 1500ppm; at a solid-liquid ratio of 1:1, 3kg of chemical formula LiNi 0.92 Co 0.05Mn 0.03 The O2 positive electrode material was added to the above-mentioned mixed solution, stirred and washed for 1 minute, and immediately solid-liquid separation was performed using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3 hours, and then sintered at 600°C for 8 hours under pure oxygen to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0036] Comparative Example 3
[0037] 7.3 g of LiOH·H2O (concentration 56.7%) was added to 2.95 L of pure water and stirred to form a solution, and 60 g of aluminum sol (solid content 10%) was added to form a LiOH-aluminum sol mixed solution, wherein: Li + The concentration is 400ppm, the concentration of hydrated alumina is 0.2wt%; weigh 3kg of chemical formula LiNi 0.92 Co 0.05 Mn 0.03 The O2 positive electrode material was added to the above-mentioned mixed solution, stirred and washed for 1 minute, and immediately solid-liquid separation was performed using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3 hours, and then sintered at 600°C for 8 hours under pure oxygen to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0038] Comparative Example 4
[0039] 82g LiOH·H2O was added into 2.95L pure water and stirred to form a solution, and 60g aluminum sol (solid content was 10%) was added to form a LiOH-aluminum sol mixed solution, wherein: Li + The concentration is 4500ppm, the concentration of hydrated alumina is 2wt%; weigh 3kg of chemical formula LiNi 0.92 Co 0.05 Mn 0.03 The O2 positive electrode material was added to the above-mentioned mixed solution, stirred and washed for 1 minute, and immediately solid-liquid separation was performed using a positive pressure filter press. The solid powder obtained after separation was dried at 150°C for 3 hours, and then sintered at 600°C for 8 hours under pure oxygen to obtain a high-nickel positive electrode material with low residual alkali and alumina coating.
[0040] Test Results
[0041] Detection of residual alkali on the surface of high-nickel positive electrode material: first weigh 5g of powder material and 95g of pure water and dissolve them in a beaker, and place the beaker on a magnetic stirrer and stir for 20 minutes. Filter to obtain the filtrate, take 10mL of the filtrate and titrate with 0.05mol / L standard solution HCl, and calculate the amount of LiOH and Li2CO3.
[0042] The products treated in Examples 1-4 and Comparative Examples 1-4 were tested for residual alkali on the surface, and the results are shown in Table 1 below:
[0043] Table 1
[0044] LiOH(ppm) <![CDATA[Li2CO3(ppm)]]> Total alkali (ppm) Example 1 1982 913 2895 Example 2 2134 935 3069 Example 3 1881 1306 3187 Example 4 2548 745 3293 Comparative Example 1 2046 947 2993 Comparative Example 2 2383 1431 3814 Comparative Example 3 2042 1379 3421 Comparative Example 4 1777 1280 3057
[0045] It can be seen from Table 1 that compared with the water washing process of Comparative Example 1, the alkali content of other embodiments and the comparative example is similar, indicating that washing the high-nickel positive electrode material with the LiOH-aluminum sol mixture does not cause an increase in residual alkali. On the contrary, immersing the high-nickel positive electrode material in the LiOH-aluminum sol mixture can effectively remove LiOH and Li2CO3 on the surface of the high-nickel positive electrode material, thereby achieving the effect of reducing residual alkali.
[0046] Button test: CR2025 button battery was used for assembly and electrochemical performance evaluation. The positive electrode material was SP:PVDF=90:5:5, and the negative electrode was lithium metal. Under the test conditions of 3.0-4.3V, the battery's discharge capacity at 0.1C (nominal capacity of 200mAh / g), initial efficiency and 1C cycle performance (high temperature of 45°C) were evaluated.
[0047] The positive electrode materials sintered in Examples 1-4 and Comparative Examples 1-4 were used to assemble secondary batteries and subjected to a charge test. The results are shown in Tables 2 and Figure 1 As shown:
[0048] Table 2
[0049]
[0050] As shown in Table 2, the discharge capacity and initial efficiency of 0.1C of Examples 1-4 and Comparative Example 2 are both relatively high, that is, the alkaline solution Li concentration of 500-4000ppm can prevent the migration of Li+ in the lattice, which is beneficial to the performance of the material capacity after water washing; Figure 1 The 50 high temperature cycle retention rates of Examples 1-4 are all around 95%, and the cycle of Comparative Example 2 is not as good as that of Example 1, which is related to the fact that it is not coated with alumina.
[0051] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for reducing residual alkali and coating on the surface of high-nickel positive electrode materials, characterized in that: The following steps are involved: The high-nickel positive electrode material is placed in a LiOH-aluminum sol mixed solution, mixed and stirred, filtered and dried, and then the dried product is sintered to obtain a low-residual alkali and alumina-coated high-nickel positive electrode material.
2. The method according to claim 1, characterized in that The LiOH-aluminum sol mixed solution is prepared by dissolving LiOH in pure water to form an alkaline solution, and then adding aluminum sol to mix and stir.
3. The method according to claim 2, characterized in that The alkaline solution contains Li + The concentration is 500-4000ppm.
4. The method according to claim 1, characterized in that: The mass ratio of the high-nickel positive electrode material to the LiOH-aluminum sol mixed solution is 1:(0.6-2).
5. The method according to claim 1, characterized in that The chemical formula of the aluminosilicate sol is a(Al2O3·nH2O)·bH x ·cH2O, where b < a, c, n, and Al2O3·nH2O is hydrated alumina; the concentration of hydrated alumina in the LiOH-aluminosilicate sol mixture is 0.2-2 wt%.
6. The method according to claim 1, characterized in that The stirring time after mixing is 1-5 minutes.
7. The method according to claim 1, characterized in that The drying temperature is 100℃-150℃, and the time is 3-6h; the sintering atmosphere is oxygen, the temperature is 500℃-600℃, and the time is 3h-8h.
8. The method according to claim 1, characterized in that The composition of the high nickel positive electrode material is LiNi x Co y Mn z Me 1-(x+y+z) O2, wherein x≥0.8, 0≤y≤0.2, 0≤z≤0.2, x+y+z≤1, and Me includes one or more of Zr, Mg, Al, Ga, Ti, Nb, Mo, and W.
9. A low-residual-alkali and alumina-coated high-nickel positive electrode material obtained according to the method of any one of claims 1 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises a low residual alkali and alumina-coated high nickel positive electrode material prepared by the method of any one of claims 1 to 8 or a low residual alkali and alumina-coated high nickel positive electrode material according to claim 9.
Citation Information
Patent Citations
Method for preparing sub-micron gamma-LiAlO2 powder from nano hydrated alumina
CN101973566A
High-safety lithium ion battery cathode material and its preparation method
CN102820471A
Method for preparing high-nickel long-cycle single-crystal lithium ion battery positive-pole material
CN110451585A
Cited By
Method for reducing residual alkali on surface of high-nickel positive electrode material and for coating, and prepared high-nickel positive electrode material and secondary battery
WO2026144077A1